2017
DOI: 10.18632/oncotarget.17380
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hepatic steatosis on the progression of chronic hepatitis B: A prospective cohort and in vitro study

Abstract: AimTo characterize the effect of hepatic steatosis (HS) on the progression of chronic hepatitis B.MethodsA total of 162 chronic hepatitis B (CHB) patients confirmed by liver biopsy were involved in this study. All subjects were prospectively followed-up for 5 years in real-life clinical practice. Fibrosis stage was determined using aspartate aminotransferase-to-platelet ratio index (APRI). The end-point was cirrhosis, liver cancer or death. The effects of steatosis on the biological behavior of hepatocellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 26 publications
2
23
0
Order By: Relevance
“…Elevated BMI in association with hepatitis could support the diagnosis of underlying nonalcoholic liver disease (NAFLD). Several studies have suggested that NAFLD can have a synergistic effect on viral oxidative stress in hepatocytes, ( 14 ) predisposing children to higher liver enzyme elevations during a viral infection. The only patient who developed multiorgan failure and severe hepatitis was obese.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated BMI in association with hepatitis could support the diagnosis of underlying nonalcoholic liver disease (NAFLD). Several studies have suggested that NAFLD can have a synergistic effect on viral oxidative stress in hepatocytes, ( 14 ) predisposing children to higher liver enzyme elevations during a viral infection. The only patient who developed multiorgan failure and severe hepatitis was obese.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Chen et al 21 studied oleic acid–induced hepatic steatosis cells in vitro and found that cell steatosis does promote proliferation and migration of HCC cells. However, clinical results in follow-up patients regarding HCC development and CHB do not show similar data.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, NAFLD, which includes steatosis with or without necroinflammation, has emerged as another major and common cause of liver injury in the general population. As it can result in hepatocellular carcinoma, cirrhosis, and liver failure,9 it is one of the most targeted liver disorders for prevention and treatment. Researchers have concluded that host factors including metabolic syndrome provide conditions for developing fatty liver and steatohepatitis in patients with CHB,16 and liver fibrosis may be more frequent in this situation 20.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have revealed that steatosis (such as NAFLD) and chronic viral hepatitis (including chronic HBV [CHB]) have a synergistic effect on aggravating liver injury through oxidative damage, so their coincidence could promote hepatic fibrosis and hepatocellular carcinoma 7,9. On the other hand, according to various previous studies, NAFLD is strongly associated with obesity, type 2 diabetes, and metabolic syndrome,10,12 especially when in combination with CHB 13,16.…”
Section: Introductionmentioning
confidence: 99%